Quantitative methods for health research a practical interactive guide to epidemiology and statistics - Bruce, Nigel; Pope, Daniel; Stanistreet, Debbi (John Wiley & Sons, 2008)
Quantitative Research Methods for Health Professionals: A Practical Interactive Course is a superb introduction to epidemiology, biostatistics, and research methodology for the whole health care community. Drawing examples from a wide range of health research, this practical handbook covers important contemporary health research methods such as survival analysis, Cox regression, and meta-analysis, the understanding of which go beyond introductory concepts. The book includes self-assessment exercises throughout to help students explore and reflect on their understanding and a clear distinction.